Essays on Values and Practical Rationality Ethical and Aesthetical Dimensions - Marques, António; Sàágua, João (Lisbon Philosophical Studies - Uses of Languages in Interdisciplinary Fields, 2017)
The essays presented here are the outcome of research carried out by members of IFILNOVA (Institute for Philosophy of New University of Lisbon) in 2016. The IFILNOVA Permanent Seminar seeks to show how values are relevant to humans (both socially and individually). This seminar is the 'place' where different research will converge towards a unified viewpoint. This includes the discussion of the following questions: What is the philosophical contribution to current affairs and decisions that depend crucially on values? Can philosophy make a difference, namely by bringing practical reason to bear on these affairs and decision? And how to do it? Which are our scientific 'allies' in this enterprise; psychology, communication sciences, even sociology and history? This volume shows the connection between practical rationality and values and covers the dimensions ethics, aesthetics and politics.